2008
DOI: 10.1002/app.27964
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene homo‐ and copolymerization over MgCl2‐TiCl4 catalysts: Polymerization kinetics and polymer particle morphology

Abstract: Three procatalysts of the MgCl 2 /TiCl 4 type, differing mainly in their morphological characteristics, were investigated in ethylene polymerization and ethylene-1-butene copolymerization. Apparently, hydrogen has an intrinsic and general deactivating effect but it can also play an activating effect in homopolymerization. This peculiarity was found to be related to a catastrophic breakage of the polymer/catalyst particles during growth and thus to the exposure of new active centers. In this case the kinetic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 31 publications
(80 reference statements)
0
39
0
Order By: Relevance
“…High porosity of the support generally leads to relatively easy diffusion of the monomer, and recent studies have demonstrated that pore size is more important than overall porosity in this respect. [19] In the present work, the pore size distributions of MgCl 2 /AlR n (OEt) 3Àn supports were determined by mercury porosimetry, giving the results shown in Figure 3. Further data are given in the Supporting Information, along with pore size distributions of the MgCl 2 Á nEtOH support precursors.…”
Section: Resultsmentioning
confidence: 99%
“…High porosity of the support generally leads to relatively easy diffusion of the monomer, and recent studies have demonstrated that pore size is more important than overall porosity in this respect. [19] In the present work, the pore size distributions of MgCl 2 /AlR n (OEt) 3Àn supports were determined by mercury porosimetry, giving the results shown in Figure 3. Further data are given in the Supporting Information, along with pore size distributions of the MgCl 2 Á nEtOH support precursors.…”
Section: Resultsmentioning
confidence: 99%
“…2015, 216, 1472−1482 Table 2 ); B) with Cat1 at different cocatalyst concentration (corresponding to Run 1,3,8,9 in Table 2 ). Table 2 ); B) with Cat3 at different cocatalyst concentration (corresponding to Run 17,18,23 in Table 2 ).…”
Section: Ethylene/1-hexene Copolymerization and Characterization Of Tmentioning
confidence: 99%
“…[ 18,19 ] Further investigation is still needed in order to elucidate the comonomer effects for Ziegler-Natta catalysts.…”
Section: Ethylene/1-hexene Copolymerization and Characterization Of Tmentioning
confidence: 99%
“…The obtained polymer was recovered by re-precipitation in acetone/ methanol mixture at 0 8C. The content of butyl branches as a result of 1-hexene incorporation was determined by 13 C NMR (Bruker 400 MHz). [19] …”
Section: Polymerizationmentioning
confidence: 99%